THROUGH THE LENS OF SOCIAL JUSTICE THEORY: A CASE STUDY OF TEACHERS' RESPONSES TO STUDENTS' CHALLENGING BEHAVIORS - (:unkn) unknown (My University, 2011)
The aims of social justice in education are defined and procedurally mandated in tenets of special education law. The history of special education services is replete with examples of underrepresentation and overrepresentation of student populations. This case study sought to understand teachers' responses to students' challenging behaviors and their subsequent use of referrals for students for special education services through the lens of social justice theory. Teacher pre-interview questionnaires, interviews, surveys, and archival data were collected and analyzed for meaning. Findings and themes for the study revealed teachers' experiences with students who demonstrate challenging behaviors prompt referrals based on specific criteria, indicate needs for more and better training to support students with special needs, teachers address problematic and challenging behaviors, and teachers are unsure of the meaning and terms of educational equity and social justice, as well as the implications for students with special needs.
Keywords: Teachers of problem children--Psychology; Teaching--Social aspects; Children with social disabilities--Education; Problem children--Education; Problem youth--Education; Social justice